2021
DOI: 10.3389/fpsyt.2021.744180
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Autistic Traits Between Iranian Students With Different Ethnic Backgrounds: A Cross-Cultural Study

Abstract: Autistic traits (ATs) include symptoms associated with autism spectrum conditions (ASCs), which are assumed to be continuously distributed across the general population. Studies have indicated the cultural differences in the expression of ATs. Notwithstanding, our literature review indicated that studies on cross-cultural differences in the expression of ATs included samples from different countries. This is the first study designed to compare the expression of ATs between different ethnicities from the same c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…At this point, we also want to mention that in the German sample a clearer sex‐effect on autistic traits could be observed than in the Chinese sample; in particular, in the German sample, males showed on average significantly higher autistic traits than females. Previous research indicated that the expression of autistic traits could be influenced by ethnicity and cultural context of investigated individuals (Elhami Athar et al., 2021 ; Wakabayashi et al., 2006 ). To illustrate this: Freeth, Sheppard et al.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, we also want to mention that in the German sample a clearer sex‐effect on autistic traits could be observed than in the Chinese sample; in particular, in the German sample, males showed on average significantly higher autistic traits than females. Previous research indicated that the expression of autistic traits could be influenced by ethnicity and cultural context of investigated individuals (Elhami Athar et al., 2021 ; Wakabayashi et al., 2006 ). To illustrate this: Freeth, Sheppard et al.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, Iran is a diverse country with multiple ethnic/linguistic groups, each having its own distinct language, traditions, and folklore (for a review see Elhami Athar et al, 2021 ) which could influence the manifestation and prevalence of psychopathic traits. In this vein, the study of Sajjadi et al ( 2023 ) included a combined sample of university students from Tehran and Ahvaz.…”
Section: Introductionmentioning
confidence: 99%